Plato's Symposium : a reader's guide - Cooksey, Thomas L. (Continuum reader's guides., 2010)
In many regards the dialectical counterpart of the Republic, the Symposium is one of the richest and most influential of the Platonic dialogues, resonating not only with Western philosophy, but also with literature art and theology. While Plato ostensibly dramatizes a humorous account of a drinking party, he presents a profoundly serious explication of Eros that challenges the limits of reason, the nature of gender, identity and narrative form. € Plato's Symposium : A Reader's Guide presents a concise and accessible introduction to the text, offering invaluable guidance on: - Historical.